(untitled) (Collaborate Engineering Daily Book Series, 2025)
The transition to renewable energy encourages the acceleration of the development of marine energy such as waves, currents, and tides. Despite being categorized as low-carbon energy, marine energy infrastructure installations raise critical questions regarding their impact on vulnerable coastal ecosystems. This perspective article aims to critically analyze the environmental aspects of marine energy installations and offer a mitigation approach based on the principles of prudence and adaptive management. The perspective raised emphasizes that the success of marine energy is not only determined by technological efficiency, but also by the integration of ecological considerations in project planning, design, and operation.